A teenager with life-threatening abdominal pain - Giorgia Carlone; Valerio Caracino; Iole Mancini; Alessandra Scaparrota; Daniela Trotta; Maurizio Arico (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
A previously healthy 17-year-old boy was admitted to our emergency department for fever, pharyngitis with cervical lymphadenopathy, abdominal pain, and vomiting for three days. On admission, he was afebrile and his vital signs were normal. Yet, following another vomiting episode, he developed another bout of abdominal pain. C-reactive protein was normal, haemoglobin 14.1 g/dl, WBC 15 x 103/µL, platelets 138 x 103/µL, AST 522 U/L, ALT 341 U/L, total bilirubin 4.75 mg/dl, with direct bilirubin 3.4 mg/dl; LDH level 689 U/L.